The Impact of Carboxymethyl Cellulose Concentration on the Properties of Super Red Dragon (Hylocereus costaricensis) Fruit Jam - Ricky Rikardo; Umi Rosidah (Jurnal Ilmu Pertanian Indonesia, 2025)
The purpose of this study was to assess the physical, chemical, and sensory features of super red dragon fruit jam using a completely randomized design (CRD) with one factor and six treatments in triplicates. The treatment was CMC concentration (0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%). Physical factors (viscosity and spreadability), chemical properties (total soluble solids, pH, and moisture content), and sensory properties (hedonic texture test) were all evaluated, using analysis of variance (ANOVA). Treatments with a significant effect (p < 0.05) were further tested using the Honest Significant Difference (HSD) test for physical and chemical characteristics, and the Tukey test for sensory characteristics (p < 0.05). CMC concentration significantly impacted (p < 0.05) viscosity, spreadability, total dissolved solids, pH, moisture content, and hedonic texture test findings. The 0.3% CMC treatment had the highest sensory score (3.48), viscosity (63.60 Pa·s), spreadability (21.37 cm), and chemical properties (total soluble solids 65.20 °Brix, pH 3.44, moisture content 31.57%). The total soluble solids and pH values in the 0.3% CMC treatment of super red dragon fruit jam met the SNI 3746-2008 requirements. This study suggests ways to increase the economic value of super red dragon fruit through jam processing, potentially reducing farmer losses and expanding the usage of CMC with other fruit varieties to diversify fruit jam products. Keywords: carboxymethyl cellulose, Fruit jam, red dragon fruit